2019
DOI: 10.1055/s-0039-1677740
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Interosseous Neurectomy Alternative for Treating Chronic Wrist Pain

Abstract: Background Wrist denervation is one of the several available options for treating chronic wrist pain; partial wrist denervation performed through a single dorsal incision by resecting the distal posterior interosseous nerve provides good outcomes. Questions/Purposes This study evaluated the results of posterior interosseous neurectomy (PIN) in patients with chronic wrist pain secondary to scaphoid nonunion advanced collapse (SNAC) and scapholunate advanced collapse (SLAC). Methods In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 12 publications
5
11
4
Order By: Relevance
“…9 Our percutaneous procedure is an evolution of the traditional partial denervation technique, providing advantages of being less invasive, with no significant scarring or negative cosmetic effects; not requiring restriction of movement or activities in the postoperative phase; can be performed in medical office and not in the operating theater; and does not preclude the subsequent use of invasive surgical procedures, as needed. Consistent with previous research, we did not identify any complications associated with partial denervation of the wrist, [10][11][12][13][14][15][16][17] compared with complications associated with total denervation of the wrist, [18][19][20] which include dysesthesia, painful neuroma, and complex regional pain syndrome.…”
Section: Discussionsupporting
confidence: 89%
“…9 Our percutaneous procedure is an evolution of the traditional partial denervation technique, providing advantages of being less invasive, with no significant scarring or negative cosmetic effects; not requiring restriction of movement or activities in the postoperative phase; can be performed in medical office and not in the operating theater; and does not preclude the subsequent use of invasive surgical procedures, as needed. Consistent with previous research, we did not identify any complications associated with partial denervation of the wrist, [10][11][12][13][14][15][16][17] compared with complications associated with total denervation of the wrist, [18][19][20] which include dysesthesia, painful neuroma, and complex regional pain syndrome.…”
Section: Discussionsupporting
confidence: 89%
“…The most common complications were soft tissue complications (9.3%) and symptomatic implants (8.8%). These reoperation and complication rates are similar to prior studies: Reigstad et al included 76 Symptomatic implant, n (%) 12 (27) Implant failure, n (%) 8 (20) Infection, n (%) 7 (17) Nonunion, n (%) 6 (15) Ulnar impaction, n (%) 2 (4.9)…”
Section: Discussionsupporting
confidence: 85%
“…The PIN innervates the dorsal capsule so, in theory, neurectomy could reduce the pain patients experience in this area; alternatively, surgeons who perform a PIN neurectomy may perform a more thorough preparation of the fusion bed and an association may not be causal. [19][20][21] Similar findings were reported by van Hernen et al who found that performing an anterior interosseous nerve and/or PIN neurectomy at the time of proximal row carpectomy was associated with lower rates of conversion to wrist arthrodesis. 22 In addition, Wagner et al reported reduced pain, improved functional outcomes, and a higher rate of wrist joint preservation in patients with arthritis who underwent a proximal row carpectomy and a concomitant neurectomy procedure.…”
Section: Discussionsupporting
confidence: 81%
“…The level of evidence is low regarding the effect of different types of wrist denervation and meta-analyses have been impossible to perform due to heterogeneity of the reported outcome variables (Chin et al., 2020; Kadhum et al., 2020; Smeraglia et al., 2020). The improvements in PROMs in this study are considerably smaller than previous reports on partial wrist denervation (Abdelaziz et al., 2019; Hofmeister et al., 2006; O'Shaughnessy et al., 2019; Riches et al., 2014). Comparison between previous studies and ours is complicated by different indications for surgery, diverse PROM scales and the fact that none of these studies reported PROMs at specified timepoints postoperatively, only at last follow-up visit, which varied considerably in time both within and between studies.…”
Section: Discussioncontrasting
confidence: 82%
“…(2006) investigated patients with wrist instability and reported a mean DASH improvement of 15 points in 50 wrists 24–42 months after AIN and PIN resection. Abdelaziz et al. (2019) reported an average improvement of 15 points in DASH score 12–30 months after PIN denervation in 30 wrists with SLAC/SNAC osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%